PSYCHOSOCIAL IMPLICATIONS OF CANCER SCREENING IN GENETIC CANCER SYNDROMES: Cancer Screening in Genetic Cancer Syndromes - Parvez, Tariq; Parvez, Babar; Al-Taifi, Abdullah Ali (Pakistan Armed Forces Medical Journal, 2007)
INTRODUCTIONGenetic mutations linked with cancer are increasingly found. Improvements in gene mutation screening will increase the sensitivity, accuracy and therefore the applicability of genetic testing in these conditions [1]. Similarly their use for screening is becoming widespread. Genetic analysis is now becoming available to diagnose such mutations which predispose to inherited cancer diseases. Among them some more important are hereditary breast and ovarian cancer (HBOC), hereditary non-polyposis colon cancer (HNPCC) and familial adenomatous polyposis (FAP). Familial colorectal cancer (CRC) is noted in about 15% of CRC cases, and this type occur at age less than 50 years. Familial adenomatous polyposis (FAP) and hereditary non-polyposis colon cancer (HNPCC) account for about 40% of familial cases [2].